Analisis Pergeseran Terjemahan dalam Lirik Lagu ‘To the Bone’ dan ‘One Only’ karya Pamungkas - Fatayati, Fina; Yamayanti, Kadek Putri (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study is aims to analyze and identify the forms of translation shifts in the lyrics of the songs To the Bone and One Only by Pamungkas, translated from English to Indonesian. The method employed is qualitative descriptive with a text analysis approach. The translation were conducted by the researcher and analys using Catford’s (1965) theory of translation shifts, which included level shifts and category shifts, namely structure shift, class shift, unit shift, and intra-sistem shift. The analysis result indicates that all five types of shifts were found in both of songs lyrics. In the translation process, these shift employed to ensure the original meaning, adjust to the natural structure of the target language, preserve emotional elements, and maintain the art quality of the song lyrics. The findings of analysis emphasize that the application of shifts in translation is an important strategies for effectively transferring message across languages and cultures, particularly in the context of poetic and expressive the song lyrics. Keywords: Lyrics Song, Translation Shifts, Translation of Songs Lyrics